Usage of E-Resources Among the Students of GCUF Library - Wahid Ullah; Muhammad Usman; Adnan Ullah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Assessing the state of the electronic means and facilities delivered by the Government College University Faisalabad (GCUF) library in Faisalabad was the intent of this study. This study investigates the reasons for using electronic resources, highlights their benefits, outlines the various topics they cover, assesses the satisfaction of GCUF users, identifies the challenges they face when retrieving these means, and explores the alleged effect of electronic resources on users. In addition, a quantitative approach was employed, utilizing the survey method. Moreover, it illustrates the findings derived from survey-based research that examined the utilization of digital resources as well as their impact on GCUF users. In addition, SPSS was utilized to conduct a descriptive analysis of the research constructs in order to determine the study's outcomes